Constraint or Warning? Health Shocks and Dietary Habits Among Older Adults in China - Keshan Liu; Yiwei Liu (Research on Aging, 2026)
Health shocks may reshape health behaviors in later life, yet their implications for dietary habits remain insufficiently understood. Using six waves of the Chinese Longitudinal Healthy Longevity Survey from 2002 to 2018, this study examines the association between serious illness episodes and dietary diversity among Chinese older adults. The results show that health shocks are significantly associated with lower dietary diversity. This association remains stable across sensitivity analyses. Heterogeneity analyses further indicate that the negative association is stronger among the oldest adults and those with a higher chronic disease burden. Mechanism analyses suggest that financial condition, physiological functioning, and outdoor activity partly account for the association. These findings suggest that, among older adults in China, health shocks may operate more as constraints that reduce the capacity to maintain diverse diets. Post-illness care should therefore integrate nutritional support, functional recovery, and community-based assistance, especially for older adults with greater health vulnerability.